Validating the Effectiveness of the Mandarin Pronunciation Guide among Malay Learners - Chong, Ah Kow; Yong, Ying Mei (Universiti Malaysia Pahang, 2014)
This paper reports on a study which was conducted to validate the effectiveness of a guidebook entitled “Mandarin Pronunciation Guide with a Comparison of English and Malay words.” Many authors (i.e. De Mente, 2006; Peters, 2006; Sharma, 2007) have used English phonetic to explain Mandarin pronunciation. However, no study has been conducted to prove the effectiveness of using English phonetic to learn Mandarin. Mandarin Pronunciation Guide, which content includes using similar corresponding English and Malay sounds, is a guidebook which is written for Malay and English speaking students who learn Mandarin as a foreign language. This study therefore aimed to verify the effectiveness of the guidebook as used among students of a public university in Malaysia. Participants were fifteen Malay students who were asked to use the guidebook. Pre-test and post-test were administered before and after the utilisation of the guidebook where participants were requested to record their pronunciation of 100 Chinese words. The results showed a significant improvement among participants which validated the effectiveness of the Mandarin Pronunciation Guide for use among Malay learners.